Ziconotide inhibits KCL-induced increase in intracellular calcium in rat sensory neurons: A peripheral mechanism of analgesic action - Kuzgun, Tu?rul K.; Özcan, Mete; Alçin, Ergül; Serhatlio?lu, Ihsan; Özcan, Sibel; Kaçar, Emine; Ayar, Ahmet (Turkiye Klinikleri, 2013)
Objective: Ziconotide, a novel non-opioid intrathecal analgesic agent with higher analgesic activity than morphine, has been recently approved for the treatment of severe and cronic pain. However, the exact cellular mechanism of the analgesic effects of ziconotide is not well documented. The aim of this study was to investigate the effects of ziconotide on KCl-induced intracellular calcium ([Ca2+]i) signaling in cultured rat dorsal root ganglion (DRG) neurons. Material and Methods: DRG neurons were grown in primary culture, following enzymatic and mechanical dissociation of ganglia from 1 or 2-day-old Wistar rats. DRG neurons were loaded with calcium-sensitive dye Fura-2 AM (1 ?mol). Initialy calcium-sensitive dye loaded cells were stimulated with application of KCl (30 mM) alone (control). Then, ziconotide (1 nM,10 nM and 1 ?M)+KCl were applied. Finally, these cells were stimulated with application of KCl again and intracellular calcium ([Ca2+]i) responses were quantified by the changes in the ratio of 340/380 nm using fluorescence calcium imaging system. Results: Ziconotide [1 nM (n=17), 10 nM (n=23) and 1 ?M (n=37)] dose-dependently reduced the increase of [Ca2+]i which was elicited by 30 mM KCl (high K+) in a rather irreversible manner. Moreover, pretreatment with 1 ?M ziconotide effectively prevented [Ca2+]i response to the high K+. Conclusion: It was concluded that ziconotide reduced the membrane depolarisation-induced increase in [Ca2+]i, in concentration dependent and a partially irreversible manner in rat DRG neurons, providing evidence for peripheral antinociceptive action of this drug. The effects on [Ca2+]i may indicate that ziconotide reduces release of pro-nociceptive neurochemicals in the peripheral pain pathway. © 2013 by Türkiye Klinikleri.
Zikonotid si{dotless}çan duyusal nöronlari{dotless}nda KCL ile İndüklenen hücre İçi kalsiyum arti{dotless}şi{dotless}ni{dotless} İnhibe eder: Analjezik etkinli?in bir periferal mekanizmasi{dotless}
Keywords: Calcium; Ganglia; Pain; Spinal; Ziconotide